Role of Tonsillectomy in PFAPA Syndrome: A Literature Review and Retrospective Study - Gomes, Pedro (2022)
Objective: Literature review and compare the pharmacological therapeutics effectiveness with the tonsillectomy in the disease remission.  Material and methods: Retrospective analysis of clinical data (age, gender, clinic, family history), types of treatment (pharmacological and/or surgical), time of remission (after medical and surgical treatment) and remission in the 1st, 3rd and 6th month after tonsillectomy in children with PFAPA syndrome evaluated at Hospital Pedro Hispano between January 2016 and December 2021.  Results: Nine children were evaluated (56% female, 44% male) aged between 1 and 4 years old (mean age 1.9 ± 1.3 years). At diagnosis, the mean number of weeks of remission was 4.0 ± 1.8. After corticotherapy it was 3.88 ± 1.0 and after tonsillectomy it was 50.6 ± 33.8 weeks. Conclusion: Tonsillectomy has demonstrated to be a very useful therapeutic option in the disease’s remission in children with PFAPA syndrome.